Citizens’ Councils, Conservatism and White Supremacy in Louisiana, 1964-1972 - Rebecca Brückmann (European Journal of American Studies, 2019)
This article examines the development of Massive Resistance, in particular Citizens’ Councils, in Louisiana after the council movement in the South had passed its zenith when being unable to prevent the passage of federal civil rights and voting rights legislation. This article argues that grassroots white supremacist groups in Louisiana faced a winding path of decline and revitalization, and a number of councils proved adaptive to the changing political, social, and economic landscape by devising activist strategies that focused on direct action, white voter registration, and tapping into broader conservative discourses on law and order, welfare, and morality. Similar to questions about a “long civil rights movement,” white supremacist resistance against the civil rights movement did not vanish in the latter half of the 1960s but transformed its rhetoric while seeking to align with the conservatism.